2009
DOI: 10.1159/000242357
|View full text |Cite
|
Sign up to set email alerts
|

Allergenic Differences among Pollens of Three <i>Salsola</i> Species

Abstract: Background: Sensitivity to Chenopodiaceae is a frequent cause of allergic respiratory diseases in geographic areas where sensitization to Salsola kali and Chenopodium album has been reported. The objective of this study was to evaluate the pattern of sensitization to 3 Salsola species in patients residing on the Mediterranean coast of south-eastern Spain. Methods:S. kali, S. vermiculata and S. oppositifolia pollen extracts were prepared. Patients reporting respiratory and/or cutaneous symptoms were skin prick … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…found that the frequency of sensitization to Timothy grass pollens in males in series was 56%, while in females, it was 70.6%, with no significant difference in between [ 28 ]. Pollens sensitizations were the most representative aeroallergen sensitization (44.9%) in Portugal and in southwest Germany [ 29 , 30 ]. Nevertheless, it was 87.1% in Kuwait [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…found that the frequency of sensitization to Timothy grass pollens in males in series was 56%, while in females, it was 70.6%, with no significant difference in between [ 28 ]. Pollens sensitizations were the most representative aeroallergen sensitization (44.9%) in Portugal and in southwest Germany [ 29 , 30 ]. Nevertheless, it was 87.1% in Kuwait [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although S. kali is considered the main allergenic pollen from Salsola sp., and their pollen allergens have been studied extensively in the last years [6], other Salsola sp. like S. oppositifolia and S. vermiculata have recently shown an important allergenic capacity [33]. …”
Section: Discussionmentioning
confidence: 99%
“…Botanical similarities, coincident pollination periods and mainly small, spherical and periporate pollen grains do not allow discrimination of pollen grains from different species by optical microscopy. In addition, only C. album and S. kali [6], and recently S. oppositifolia [16] on the Mediterranean coast of Spain and A. retroflexus in Iran [17], have been associated with allergic symptoms. Previous published studies have described a significant time lag between pollen counts and symptom scores in S. kali -monosensitized patients [15].…”
Section: Discussionmentioning
confidence: 99%
“…Recently published papers have suggested that other Chenopodiaceae species, which pollinate in different periods, could also contribute to allergic symptoms [16,17]. …”
Section: Introductionmentioning
confidence: 99%